STRATEGI PEMBERDAYAAN PETERNAK SAPI PERAH DALAM MENINGKATKAN POEREKONOMIAN KELOMPOK NGUDI LUHUR II DI KELURAHAN RANDUACIR KECAMATAN ARGOMULYO KOTA SALATIGA - Widyanti Okta, Okta Widyanti; Imam Subqi (Yayasan Baitul Hikmah al-Zain, 2025)
This study aims to identify empowerment strategies implemented by the Ngudi Luhur II Group to improve the economy through dairy farming in Randuacir Village, Argomulyo District, Salatiga City, and analyze its economic impact. The research method used is descriptive qualitative, with data collection techniques through interviews, observations, and documentation. The results show that this group has implemented several empowerment strategies, such as technical training and feed management, cooperative systems for access to capital and financial management, product diversification, collective marketing, and the use of modern technology. This empowerment program successfully increased members' income by 75–150%, improved milk price stability, and enhanced members' economic welfare.